PEMANFAATAN DANA BERGULIR SIMPAN PINJAM PEREMPUAN (SPP) DI KELURAHAN BATU BERSURAT KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR - Nurmi Yulis; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study entitled "Utilization of Women's Savings and Loan Revolving Fund (SPP) in Batu Bersurat Village of XIII Koto Kampar District of Kampar District". Researchers are interested in this theme because of a problem in the society about how to use the women's credit revolving fund (SPP). The purpose of this study was to determine the characteristics of the recipients of the women's credit (SPP) in the Village of Stone Inscribed and to examine the use of women's credit revolving fund (SPP) in the Village of Stone Inscribed. This type of research role in this research is quantitative descriptive which describe the results of research and analysis in order to obtain the results and then concludes. The unit of analysis in this study were all members of the women's credit (SPP) in the Village of Stone Inscribed as many as 40 people. Data collection techniques in this research is observation, interviews and documentation from the parties concerned. So as to obtain results that the use of a revolving fund women's credit (SPP) in the Village of Stone Inscribed 45% is used for productive activities and 55% is used for consumption. While the repayment ability of 55% of respondents were able to repay the loans and 45% are not able to repay the loan, so there is influence on the utilization of loan funds repayment ability.Keywords: Utilization, revolving funds, SPP